PENGARUH MUSIK POP TERHADAP MOOD MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS MUHAMMADIYAH GORONTALO DALAM MENGERJAKAN TUGAS KULIAH - Fendi Ntobuo; Adinda Kariem Kambey; Steven Saputra Suleman; Taufik Djafar; Putri Mutmainah Datau; Moh. Gimnastior Mohi (program studi psikologi, 2024)
This study aims to explore the effect of pop music on the mood of Psychology Faculty students at Muhammadiyah University of Gorontalo when completing academic tasks. Music, known as a medium for therapy and entertainment, has the potential to enhance mood and reduce emotional stress caused by academic burdens. This research employed an experimental method with a quantitative approach. A total of 22 student subjects aged 19-24 participated in this study. The FDMS-55 scale was used to measure mood changes before and after the intervention. The experimental group listened to pop music while completing tasks, whereas the control group worked without music. The Wilcoxon test results indicated a significant effect of pop music on students' mood (p = 0.036; p < 0.05). While individual differences in mood changes were observed, overall, the experimental group experienced a greater mood improvement than the control group. This study provides evidence that pop music can serve as an effective intervention to enhance mood in an academic context. Future research is advised to pay attention to the timing of the experiment to improve participants’ comfort.